2023
DOI: 10.1371/journal.pone.0279827
|View full text |Cite
|
Sign up to set email alerts
|

Public health supply chain for iron and folic acid supplementation in India: Status, bottlenecks and an agenda for corrective action under Anemia Mukt Bharat strategy

Abstract: Purpose The IFA supplementation program under the Anemia Mukt Bharat (AMB) program is one of the most ambitious nutrient supplementation programs in India. The delivery of services often suffers due to frequent stock outs and shortages. It is critical to understand the bottleneck in the supply chain adversely affecting the performance and coverage of the program. The paper attempts to identify the bottlenecks of the IFA supply chain in key areas of supply chain i.e., forecasting, procurement, warehousing and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This could be attributed to ineffective implementation of the AMB programme. Indeed, the public health supply chain for IFA supplementation under the AMB programme has received harsh criticism in the recent past ( 12 , 45 ) . For instance, Ahmed and colleagues highlighted a number of shortcomings in the delivery of AMB services which included lack of fixed distribution schedule; absence of inventory management techniques and integrated management information system, and inadequate availability of transport vehicles ( 45 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to ineffective implementation of the AMB programme. Indeed, the public health supply chain for IFA supplementation under the AMB programme has received harsh criticism in the recent past ( 12 , 45 ) . For instance, Ahmed and colleagues highlighted a number of shortcomings in the delivery of AMB services which included lack of fixed distribution schedule; absence of inventory management techniques and integrated management information system, and inadequate availability of transport vehicles ( 45 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the public health supply chain for IFA supplementation under the AMB programme has received harsh criticism in the recent past ( 12 , 45 ) . For instance, Ahmed and colleagues highlighted a number of shortcomings in the delivery of AMB services which included lack of fixed distribution schedule; absence of inventory management techniques and integrated management information system, and inadequate availability of transport vehicles ( 45 ) . Parallel to these findings, Joe and coworkers also found that the IFA supplementation coverage was relatively low among target groups including adolescents who were being supplied through a multi-departmental convergence mechanism (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The study highlights a consistent decline in the prevalence of undernutrition among women from 1998 to 2021. The literature has attributed this decline to various reasons like improved awareness, empowerment and education among women (Zajacova and Lawrence, 2018), improvement in Water, Sanitation and Hygiene practices (Kumar and Mohanty, 2023), improved access to healthcare and the impact of nutrition-specific interventions (Joumard and Kumar, 2015; Ahmad et al ., 2023). The role of government initiatives and policies in the reduction of the prevalence of undernutrition among women of reproductive age in India is also documented and is described below: Integrated Child Development Services (ICDS) have been found to have played one of the significant roles in improving the nutritional status and overall development of women and children by providing supplementary nutrition, immunization, health check-ups and pre-school education to pregnant and lactating women (Kapil, 2002).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, the National Food Security Act (NFSA) does not exclusively target women, but has made a substantial contribution by providing subsidized food grains to eligible households, ensuring better access to nutritious food for vulnerable populations, including women (Varadharajan et al ., 2014). Last but not the least, the Anaemia Mukt Bharat initiative focuses on preventing and controlling anaemia through awareness campaigns, iron and folic acid supplementation and improving dietary practices among women, thereby leading to reduced underweight prevalence (Ahmad et al ., 2023).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation